POTENSI DEKARBONISASI SEKTOR ENERGI PERUSAHAAN TAMBANG NIKEL PT XYZ DENGAN IMPLEMENTASI SISTEM MANAJEMEN ENERGI SEDERHANA - M. Eka Putra Abdillah; Rinaldy Dalimi (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to evaluate the potential implementation of the ISO 50001 Energy Management System (EnMS) at PT XYZ to achieve the decarbonization target. The focus is on strategic and technical planning, involving the analysis of internal and external issues to develop energy policies as well as the formation of energy teams. Technical planning includes energy performance reviews, energy consumption analysis, Significant Energy Users (SEUs), Energy Performance Indicators (EnPI), and operation control plans. The results of the 2022 review show that energy consumption is 947.8 thousand GJ with the main SEU in the Hauling and Mining systems, as well as Hauler and Excavator tools that consume more than 80% of Biosolar B30. EnPI level 1 shows an average energy intensity of 0.08 GJ per WMT, while EnPI level 2 results in a regression of Y=2.113X + 264924 with a determination of 0.892, making 2022 a baseline. The implementation of ISO 50001 has the potential to improve energy efficiency and reduce GHG emissions by up to 30% by 2030, with a target of saving 9.7 million liters of Biodiesel B30. The PDCA approach helps companies achieve targets by focusing on SEU systems and tools.